Business Information Systems Workshops BIS 2012 International Workshops and Future Internet Symposium, Vilnius, Lithuania, May 21-23, 2012 Revised Papers - Abramowicz, Witold; Domingue, John.; Wecel, Krzysztof; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the four workshops that were organized in conjunction with the International Conference on Business Information Systems, BIS 2012, which took place in Vilnius, Lithuania, May 21-23, 2012. In addition, the papers from the Future Internet Symposium, which was organized in conjunction with BIS 2012, are also included. BIS workshops give researchers the opportunity to share their preliminary ideas and first experimental results, and discuss research hypotheses with a highly focused audience. The 24 papers were carefully reviewed and selected from 63 submissions and were revised and extended after the event. The workshop topics covered applications and economics of knowledge-based technologies (AKTB), business and IT alignment (BITA), enterprise systems for higher education (ESHE), and formal semantics for future enterprises (FSFE). In addition, one invited paper from BITA is also included in this volume.
AKTB Workshop -- BITA Workshop -- ESHE Workshop -- FSFE Workshop -- Future Internet Symposium.
Keywords: Information technology; Business—Data processing; Application software; Artificial intelligence; IT in Business; Computer Appl. in Administrative Data Processing; Information Systems Applications (incl. Internet).; Artificial Intelligence